2019
DOI: 10.1002/pat.4724
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of boron nitride by bio‐inspired polydopamine and different chain length polyethylenimine co‐depositing

Abstract: We established a novel, easy, and versatile method of obtaining diverse and controllable interphases between epoxy resin and fillers. The method involved the co‐deposition of polydopamine (PDA) and polyethyleneimine (PEI) with different molecular lengths on boron nitride (BN) surface. The obtained PDA/PEI‐modified BN composites showed significantly improved mechanical properties, including tensile strength, toughness, and elongation at break. For example, the tensile strength, fracture toughness, and elongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The C 1s, O 1s, B 1s and N 1s elements are seen both in the survey spectra of PEI@BNNS. 45 Notably, excepting for the peaks at 397.6 eV (C–N) and 397.9 eV (B–N), a new peak was observed at 398.2 eV (B⋯N) from the N 1s spectra of PEI–BNNS, which corresponds to the intermolecular interaction between B atom in BN and the amino groups in PEI. 46 The high resolution B 1s spectra of PEI@BNNS can be divided into two major peaks located at 191.1 eV and 189.3 eV, which are correspond to the B–N and the, while the B–O bond maybe caused by the ultrasonic process.…”
Section: Resultsmentioning
confidence: 93%
“…The C 1s, O 1s, B 1s and N 1s elements are seen both in the survey spectra of PEI@BNNS. 45 Notably, excepting for the peaks at 397.6 eV (C–N) and 397.9 eV (B–N), a new peak was observed at 398.2 eV (B⋯N) from the N 1s spectra of PEI–BNNS, which corresponds to the intermolecular interaction between B atom in BN and the amino groups in PEI. 46 The high resolution B 1s spectra of PEI@BNNS can be divided into two major peaks located at 191.1 eV and 189.3 eV, which are correspond to the B–N and the, while the B–O bond maybe caused by the ultrasonic process.…”
Section: Resultsmentioning
confidence: 93%
“…Compared with the previous studies on polymer nanocomposites containing different 2D nanomaterials like graphene or MoS 2 , more efficient strengthening and toughening results were concluded in this work. As shown in the radar diagram (Figure ), the pentagons for the mechanical properties involved in this work covered entirely those of other EP nanocomposites containing different 2D nanomaterials. …”
Section: Resultsmentioning
confidence: 99%
“…Wu et al used a combination of mechanical exfoliation and chemical modification to modify h‐BN, and the result showed that the introduction of PEI enhanced the dispersibility and compatibility of h‐BN in EP, furthermore, the crosslink density of epoxy resin also improved 32 . Wang et al adjusted the interface reaction between BN and epoxy resin matrix by using diverse molecular lengths of PEI and PDA, and found that the mechanical performances of BN/PDA‐PEI had obviously improved 33 …”
Section: Introductionmentioning
confidence: 99%